Curcumin-loaded leech matrix / silk fibroin biomimetic composite tendon scaffold, and preparation method and application thereof
By using a biomimetic composite tendon scaffold made of curcumin-loaded leech matrix/silk fibroin, the problems of biosafety risks, postoperative adhesions and insufficient mechanical properties in tendon repair were solved, achieving high-quality tendon regeneration and functional recovery.
Patent Information
- Application Number
- CN202611034351.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-11-06
AI Technical Summary
Existing tendon repair materials have problems such as high biosafety risks, easy postoperative adhesion, insufficient mechanical properties, and incomplete microenvironment regulation, which cannot meet the needs of high-quality tendon regeneration and repair.
A biomimetic composite tendon scaffold using curcumin-loaded leech matrix/silk fibroin was constructed by using a modified gradient chemical decellularization process and ultraviolet cross-linking technology to create an asymmetric structure with different physicochemical properties on the inner and outer surfaces. Combined with the sustained-release function of curcumin, it simulates the natural tendon structure, synergistically regulates the immune microenvironment, and prevents postoperative adhesions.
It achieves high biocompatibility, stable wet mechanical properties, and synergistic regulation of anti-fatigue and anti-inflammatory and antioxidant properties, effectively preventing postoperative adhesions and promoting high-quality tendon regeneration and functional recovery.
Smart Images

Figure CN123038348A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a biomimetic composite tendon scaffold containing curcumin-loaded leech matrix / silk fibroin, its preparation method and application, belonging to the field of tissue engineering and biomedical materials technology. Background Technology
[0002] Tendon injuries, especially Achilles tendon ruptures, are common serious conditions in orthopedics and sports medicine, with high disability rates and poor postoperative recovery outcomes. The Achilles tendon is the densest fibrous connective tissue in the human body that bears the greatest weight and plays a crucial role in mechanical transmission. However, tendon tissue has low cell density, poor blood supply, and extremely weak endogenous regeneration capacity, making it difficult to repair itself after severe injury.
[0003] The natural healing mechanism of tendon injuries has inherent pathological defects. Following injury, a strong oxidative stress response erupts locally, triggering immune microenvironment dysregulation, manifested as a large-scale polarization of macrophages towards the pro-inflammatory M1 type, continuously inducing local inflammation. This process leads to excessive proliferation of exogenous fibroblasts, resulting in the disordered deposition of large amounts of type III collagen, ultimately forming fibrotic scars with poor mechanical properties. Simultaneously, scar tissue easily adheres to surrounding soft tissues, causing limited joint movement and loss of motor function, which is a core reason for the poor prognosis of clinical tendon repair. Therefore, relying solely on the body's self-repair cannot achieve functional tendon regeneration; there is an urgent need to develop novel functional biological scaffolds to target and optimize the repair microenvironment and reconstruct the normal tendon structure.
[0004] Currently, tendon repair materials both domestically and internationally are mainly classified into four categories: mammalian-derived decellularized matrix (dECM), synthetic polymer scaffolds, aquatic animal-derived biomatrix, and drug-loaded composite repair scaffolds. Among existing technologies, the bovine tendon decellularized graft (R-dECM) loaded with rosiglitazone, disclosed by Jin et al. in 2023, provides a reference for tendon immune-modulated repair. This approach uses decellularized bovine tendon as a matrix, loaded with the small molecule drug rosiglitazone, and inhibits M1 macrophage polarization and reduces inflammation by activating the PPAR-γ pathway. However, this approach still has several unavoidable technical shortcomings: First, existing cell matrix materials have biosafety defects: the mainstream commercial and research materials from mammals such as pigs and cattle have the risk of cross-species transmission of viruses such as mad cow disease and foot-and-mouth disease, and their biosafety is limited. Secondly, there is a general lack of physical anti-adhesion structures: existing repair scaffolds are mostly highly hydrophilic surfaces, which are prone to rapid water absorption and swelling after implantation, causing non-specific adhesion and encapsulation of fibroblasts, resulting in dense tendon adhesions, which cannot solve the postoperative adhesion problem from the root. Furthermore, scaffolds have poor wet mechanical stability: simple decellularized matrix or simple chemically coated scaffolds have rapid mechanical strength decay and weak fatigue resistance in the wet environment of the body, which cannot support the stable mechanical needs in the early stage of tendon repair, and are prone to structural disintegration and repair failure. Finally, the microenvironment regulation mechanism is singular: most existing drug-eluting scaffolds only have single anti-inflammatory and immune polarization regulation functions. Mainstream solutions, represented by R-dECM, can only inhibit the inflammatory response and cannot clear the large amount of reactive oxygen species accumulated in the early stage of tendon injury or block the oxidative stress storm. They are difficult to improve the pathological state of synergistic destruction by inflammation and oxidative damage after injury, and the repair effect is limited.
[0005] In summary, existing tendon repair techniques generally suffer from high biosafety risks, a high incidence of postoperative adhesions, insufficient mechanical properties, and incomplete microenvironment regulation, failing to meet the clinical demand for high-quality tendon regeneration and repair. To address these shortcomings, this invention aims to provide a biomimetic composite scaffold that combines high biosafety, stable wet mechanical properties, physical anti-adhesion characteristics, and synergistic anti-inflammatory and antioxidant regulatory functions. This addresses the core pain points of traditional techniques, achieving high-quality reconstruction of the Achilles tendon's anatomical structure and motor function. Summary of the Invention
[0006] To address the core issues in current tendon repair, such as poor regeneration quality (easily leading to disordered scar tissue), severe postoperative adhesions (exogenous healing is superior to endogenous regeneration), biosafety risks of xenogeneic materials (cross-species viral transmission), and the tendency of decellularized matrix to swell in vivo leading to mechanical failure, this invention aims to provide a biomimetic composite tendon scaffold loaded with curcumin-containing leech matrix / silk fibroin, its preparation method, and its application. By simultaneously improving the species origin and asymmetric physicochemical properties of the scaffold framework, it achieves the effects of simulating the anisotropic structure of natural tendons, synergistically regulating the immune microenvironment, and effectively preventing postoperative adhesions.
[0007] To achieve the above objectives, the following technical solution is provided: The first objective of this invention is to provide a method for preparing a leech matrix / silk fibroin biomimetic composite tendon scaffold carrying anti-inflammatory components, the method comprising the following steps: (1) Under light-protected conditions, methacrylamide silk fibroin was dissolved in PBS to form a polymer base solution; then, natural anti-inflammatory substances and photoinitiators were added to the polymer base solution, and the solution was subjected to ultrasonic treatment in an ice-water bath to obtain a prepolymer solution. (2) Immerse the porous leech decellularized matrix sheet completely in the prepolymer solution obtained in step (1), incubate overnight, remove it after incubation, and roll it into a cylindrical shape along the natural arrangement direction of collagen fibers. (3) The cylindrical shape obtained in step (2) is immediately placed in the UV curing system for UV crosslinking. After the crosslinking is completed, it is freeze-dried and sterilized to obtain the product.
[0008] In one embodiment, the PBS in step (1) is a phosphate buffer with a pH of 7.2-7.4.
[0009] In one embodiment, the methacrylamide silk fibroin in step (1) is commercially available or homemade.
[0010] In one embodiment, the preparation process of the methacrylamide silk fibroin in step (1) is as follows: Degummed silk fibroin was added to an aqueous solution containing lithium bromide and magnetically stirred in a constant temperature water bath to form a high-viscosity, amber-colored homogeneous silk fibroin solution. Then, glycidyl methacrylate (GMA) was slowly added dropwise to the system. After the addition was complete, the reaction was continued under light-protected conditions. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain a white, loose, sponge-like porous SilMA polymer.
[0011] In one embodiment, the concentration of the lithium bromide aqueous solution is 9-10 mol / L; the mass-to-volume ratio of degummed silk fibroin to the lithium bromide aqueous solution is 1-2:10, g / mL.
[0012] In one embodiment, the temperature in the constant temperature water bath is 50~60℃, and the stirring rate is 200~300rpm.
[0013] In one embodiment, the degummed silk fibroin and glycidyl methacrylate have a mass-to-volume ratio of 10-20:3-5, g:mL.
[0014] In one embodiment, the continued reaction time is 6-8 hours.
[0015] In one embodiment, the mass-to-volume ratio of methacrylamide silk fibroin in the polymer base solution of step (1) is 10-30% w / v, g / ml.
[0016] In one embodiment, the natural anti-inflammatory substance in step (1) includes one or more of curcumin, resveratrol, and quercetin; more preferably curcumin.
[0017] In one embodiment, the concentration of the natural anti-inflammatory substance in the prepolymer solution in step (1) is 20~100µg / mL.
[0018] In one embodiment, the photoinitiator in step (1) is lithium phenyl-2,4,6-trimethylbenzoyl phosphate (LAP), and its mass concentration in the prepolymer solution is 0.1~0.3% w / v, g / ml.
[0019] In one embodiment, the porous leech decellularized matrix sheet in step (2) is obtained by decellularizing leech epidermal tissue and then freeze-drying it.
[0020] In one embodiment, the specific preparation process of the porous leech decellularized matrix sheet is as follows: Step 1: Take a live, healthy, fresh leech and anesthetize it by placing it in an ice-water mixture. Then, cut it longitudinally along the midline of the back, peel off and thoroughly scrape away the internal digestive system, residual muscle layer and pigment layer tissue, leaving only the epidermal layer rich in connective tissue. Immerse the obtained epidermal tissue in PBS buffer at 4°C and rinse repeatedly until the washing solution is clear, then cut it into tissue blocks. Step 2: Transfer the tissue blocks described in Step 1 to centrifuge tubes and add sodium dodecyl sulfate (SDS) solution at a mass-to-volume ratio of 1-3% (w / v, g / ml). Place the tubes in a constant temperature shaking incubator and treat for 18-24 hours. After treatment, discard the waste liquid and add PBS solution containing 1% (v / v) penicillin-streptomycin. Shake and wash 3-5 times, 1 hour each time. Then add 1% (v / v) Triton X-100 solution and continue shaking and treating for 18-24 hours. After treatment, wash again with PBS solution containing penicillin-streptomycin to obtain a translucent milky white leech decellularized matrix (dLE). Step 3: Pre-freeze the dLE obtained in Step 2, and then vacuum dry it to obtain the final product.
[0021] In one embodiment, the ratio of the porous leech decellularized matrix sheet to the prepolymer solution in step (2) is 1:5~10, g:mL.
[0022] In one embodiment, the overnight incubation time in step (2) is 24 hours, the incubation temperature is 37°C, and the shaking speed is 60~80 rpm.
[0023] In one embodiment, the LED surface light source with a wavelength of 405 nm and an illumination intensity of 25 mW / cm², which is cross-linked with ultraviolet light in step (3), is continuously and uniformly irradiated for 60 seconds.
[0024] In one embodiment, the freeze-drying in step (3) specifically involves pre-freezing at -60~-80℃ and then freeze-drying at -60~-40℃.
[0025] A second objective of this invention is to provide a leech matrix / silk fibroin biomimetic composite tendon scaffold loaded with anti-inflammatory components prepared by the method described above.
[0026] A third objective of this invention is to provide the application of the aforementioned leech matrix / silk fibroin biomimetic composite tendon scaffold carrying anti-inflammatory components in the fields of medicine and biomaterials.
[0027] In one embodiment, the application is specifically in the fields of orthopedics and sports medicine. This scaffold can be used for in-situ repair of acute tendon ruptures (such as Achilles tendon rupture, rotator cuff tear, patellar tendon rupture, and flexor tendon rupture), microenvironmental regulation of chronic tendinopathy, structural reconstruction of critical-size tendon defects, and as a physical barrier to prevent postoperative adhesions of surrounding tissues. It is particularly suitable for intratendon sheath repair requiring the maintenance of gliding function and can be extended to the tendon itself. Regeneration and repair of bone interfaces (such as rotator cuff insertion and cruciate ligament insertion).
[0028] In one embodiment, the application is specifically in the field of regenerative medicine and tissue engineering. The scaffold can serve as a cell-free repair scaffold, recruiting endogenous tendon stem cells through its natural chemotaxis to achieve in-situ regeneration. It can also serve as a sustained-release carrier for drugs or active molecules, loading curcumin or other anti-inflammatory and regenerative drugs (such as rosiglitazone, BMP). 12. PDGF BB), whose biomimetic anisotropic structure can also provide design templates for other tissues that require directional cell arrangement, such as ligaments, nerve conduits, and myocardial patches.
[0029] In one embodiment, the application is specifically in the field of immune modulation and anti-inflammatory treatment. The stent can inhibit excessive inflammatory response and fibrosis caused by foreign body reaction induced by the implant. It is suitable for tendinopathy associated with autoimmune diseases such as rheumatoid arthritis, and can be used to remove reactive oxygen species for tendon defects with severe oxidative stress, such as diabetic foot tendon exposure and radiation tissue damage.
[0030] In one embodiment, the application is specifically in the field of surgery and minimally invasive surgery. The rolled-up cylindrical scaffold can be implanted through a small incision or cannula. Combined with the photocrosslinking properties of SilMA, personalized heteromorphic tendon scaffolds can be customized based on the patient's imaging data using 3D / 4D bioprinting technology. It can also be used for emergency functional reconstruction of soft tissue defects caused by war or catastrophic events.
[0031] In the research and development and transformation of biomedical materials, decellularized matrix derived from aquatic invertebrates (leeches) provides a safer alternative to traditional mammalian materials, free from religious and ethical concerns. Its design concept of "rigid collagen framework + flexible hydrogel interpenetrating network" can be extended to other soft tissue repair materials such as cartilage, skin, and blood vessels, while also being externally hydrophobic. The hydrophilic Janus coating technology can also be used for surface functionalization modification of medical devices such as artificial tendon sheaths, catheters, and sutures.
[0032] In one embodiment, the application specifically involves developing composite scaffolds into various product forms such as freeze-dried ready-to-use sterile implants, pre-rolled cylindrical tendon substitutes, or injectable hydrogel precursors, serving orthopedics, sports medicine, hand surgery, plastic surgery, trauma surgery, and rehabilitation medicine. These scaffolds can also be used in combination with autologous platelet-rich plasma, mesenchymal stem cells, exosomes, etc., to achieve synergistic effects.
[0033] Beneficial effects: Compared with existing technologies, the biomimetic composite tendon scaffold prepared in this invention precisely addresses the core pain points in the tendon repair process, such as biological risks, mechanical disintegration, postoperative adhesions, and uncontrolled inflammation, and achieves the following significant and quantifiable technical effects: (1) Excellent source safety and natural physical topology guidance (solving the risks and disordered growth problems of xenografts): This invention uses leeches with great species differences as a matrix, which fundamentally eliminates the risk of zoonotic diseases caused by mammalian matrix (such as pigs and cattle); through the improved gradient chemical decellularization process, more than 98% of the DNA is removed (the residual amount is only 21.33 ± 7.69 ng / mg, which is far below the internationally recognized safety standard of 50 ng / mg), while perfectly preserving the natural highly parallel type I collagen topology, providing a precise "directed growth track" for endogenous stem cells; (2) Excellent wet mechanical reinforcement and fatigue resistance (solving the problems of insufficient mechanical support and extreme swelling in the early stage of implantation): Swelling inhibition: The interpenetrating cross-linked network constructed with 20% SilMA precisely and significantly limited the swelling rate of the pure leech matrix, which is extremely hygroscopic, from 671.09% to approximately 323.22%, effectively preventing mechanical disintegration of the scaffold in vivo due to excessive water absorption.
[0034] Fatigue resistance enhancement: The wet ultimate failure load of the composite scaffold is increased by approximately 87.5% compared to the pure matrix. After 50 cycles of tensile testing under a high strain of up to 50%, the scaffold still maintains extremely high structural resilience, and its ultimate tensile strength (2.83 MPa) shows no significant decrease compared to the initial tensile test, perfectly matching the dynamic tension requirements in the early stages of tendon rehabilitation.
[0035] (3) “Janus Asymmetric Structure” Achieves Strong Physical Anti-Adhesion (Solving the Problem of Exogenous Scar Encapsulation and Tissue Adhesion): This invention innovatively utilizes the difference in interfacial tension of materials and the curling process to construct an asymmetric structure with drastically different physicochemical properties on the inner and outer surfaces. The outer SilMA coating has a contact angle as high as 91.80°, forming a dense hydrophobic physical barrier that effectively blocks the invasion of peripheral fibroblasts; the inner layer has a contact angle of 63.80°, maintaining hydrophilic properties and facilitating nutrient exchange; In vivo anti-adhesion effect: Animal experiments have shown that the surface of the newly formed Achilles tendon is extremely smooth and without adhesion 8 weeks after surgery, with a width of only 2.51 mm (the height is close to the normal anatomical shape), while the defect group without anti-adhesion treatment formed a dense adhesion scar with a width of up to 3.63 mm.
[0036] (4) Long-lasting anti-inflammatory and active targeted remodeling of the microenvironment (solving the problems of oxidative stress storm and polarization imbalance of M1 macrophages): Precise sustained release: The SilMA network enables curcumin to achieve a stable sustained release for up to 168 hours (7 days) locally (cumulative release of 38.57%, with no obvious burst release), precisely covering the key acute inflammatory period of damage repair; Immune reversal and recruitment promotion: This sustained-release system effectively induced macrophages to transform into reparative (M2) cells, resulting in a 58% decrease in the concentration of the pro-inflammatory factor IL-6 (down to 400.3 pg / mL) and a 60% decrease in TNF-α in vitro; it also increased the number of transmembrane migration of tendon stem cells (TDSCs) to 2.1 times that of the control group (47.67 cells / field), successfully reversing the microenvironment from "pro-inflammatory and scar-promoting" to "anti-inflammatory and regenerative"; (5) Substantial biomechanical and gait function reconstruction (final repair index) has been achieved. Gait recovery: In a rat model of large Achilles tendon defect (5mm), at 8 weeks post-surgery, the Achilles tendon function index (AFI) of the scaffold group of the present invention recovered to -3.98 ± 2.68, almost returning to the normal physiological baseline before surgery, while the simple defect control group had only a severe -16.68. Mechanical leap: The newly generated Achilles tendon induced by this invention has a dense and orderly internal collagen arrangement, and its ultimate tensile stress jumps to 8.01 ± 0.87 MPa, which is 2.9 times that of the untreated simple defect group (2.76 MPa). Attached Figure Description
[0037] Figure 1 Image showing the decellularization characteristics of F-LE and dLE; (A) Images of F-LE and dLE stained with H&E, Masson's trichrome, Sirius red, and DAPI / Col-1 immunofluorescence double staining; (BC) DNA content before and after decellularization; (D) Collagen content before and after decellularization; Figure 2 Fourier transform infrared spectra of SF and SilMA; Figure 3 Figure 1 shows the microstructure characterization and biomimetic properties analysis of the composite scaffold; (A) SEM images of cross-sections of dLE and composite scaffolds with different concentrations of SilMA-dLE; (B) SEM comparison of the outer surface and cross-section of dLE and rat decellularized Achilles tendon; (C) TEM ultrastructure comparison of dLE and rat decellularized Achilles tendon. Figure 4 The following figures characterize the static tensile mechanical properties of the composite stent: (A) Stress-strain curves of composite stents with different concentrations of SilMA crosslinking in the wet state; (B) Quantitative analysis of the ultimate tensile stress of each group of wet stents; (C) Comparison of stress-strain curves of each group of stents in the dry and wet states; (D) Quantitative analysis of the ultimate tensile strength of each group of dry and wet stents; (E) Stress-strain curves of 20% SilMA-dLE stents under different immersion times (immediate crosslinking vs. overnight immersion); (F) Quantitative analysis of the ultimate failure load of 20% SilMA-dLE stents under different immersion times. Figure 5 Characterization of the cyclic tensile mechanical properties and fatigue resistance of composite stents; (A) Comparison of stress-strain curves of each group of stents at the 1st and 50th cycles (50% strain); (B) Quantitative analysis of the ultimate tensile strength of 20%SilMA-dLE stent after the 1st and 50th cycles. Figure 6 The in vitro swelling performance of the composite scaffold is characterized as follows: (A) Swelling kinetics curves of each group of scaffolds in PBS buffer over time (0-180 minutes); (B) Quantitative analysis of swelling rate at swelling equilibrium (180 minutes). Figure 7 Image showing the wettability of the inner and outer surfaces of leech epidermis in different treatment groups; (A) Contact angle changes of fresh leech epidermis (F-LE), decellularized leech epidermis (dLE), and 20% SilMA-dLE composite scaffold at 1, 3, 10, and 30 seconds after water droplet application; (B) Quantitative analysis of the contact angle of the inner and outer surfaces of each group; (C) Rolling and shaping of the 20% SilMA-dLE composite scaffold; Figure 8 The in vitro enzymatic hydrolysis of the samples in collagenase is shown in the figure; (A) The trend of relative residual weight change of dLE and SilMA-dLE composite scaffolds of different concentrations over 7 days; (B) Quantitative analysis of the final degradation rate of each group of scaffolds on the 7th day of enzymatic hydrolysis; Figure 9 The in vitro release behavior of curcumin in the C-SilMA-dLE composite scaffold is shown in the figure; (A) the cumulative percentage release of curcumin in vitro over 168 hours (7 days); (B) the total cumulative drug release on day 7 of the release experiment. Figure 10 Image for screening curcumin concentration and evaluating the in vitro biocompatibility of composite scaffolds; (A) Cell proliferation activity after co-culturing different concentrations of free curcumin (Cur) with TDSCs for 1, 2, and 3 days (CCK-8 assay); (B) Cell proliferation activity after co-culturing different composite scaffolds with TDSCs for 1, 2, and 3 days (CCK-8 assay); (C) Live / dead staining fluorescence images after co-culturing different concentrations of free curcumin with TDSCs for 3 days; (D) Live / dead staining fluorescence images after co-culturing different composite scaffolds with TDSCs for 3 days; Figure 11 (A) Schematic diagram of the inhibitory effect of composite scaffold on LPS-induced macrophage inflammatory response; (AC) Quantitative analysis of the concentrations of IL-1β, IL-6 and TNF-α in the cell culture supernatant of each group; Figure 12 The effect of composite scaffold extract on the migration ability of TDSCs is shown in the figure; (A) Crystal violet staining images of cells migrating to the lower surface of the Transwell membrane in each group (inverted microscope, 20× magnification); (B) Quantitative statistical analysis of the number of migrating cells; Figure 13 The following are images of gait analysis and Achilles tendon function index (AFI) assessment data of rats at different time points after surgery: (A) Images of hind limb footprints of rats in each group before surgery (-2d) and at 2, 4, 6 and 8 weeks after surgery; (B) Quantitative statistical analysis of AFI index of rats in each group at different time points. Figure 14 The images show the gross morphology and biomechanical assessment data of the newly formed Achilles tendon in rats after surgery; (A) Representative gross morphological images of the newly formed Achilles tendon at 4 and 8 weeks post-surgery; (B) Quantitative statistical analysis of the width of the newly formed Achilles tendon; (C) Quantitative statistical analysis of the ultimate tensile stress of the newly formed Achilles tendon. All data are expressed as mean ± SD, ns indicates no significant difference, * indicates p < 0.05, ** indicates p < 0.01, *** indicates p < 0.001, and **** indicates p < 0.0001. Detailed Implementation
[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. The specific embodiments described below further illustrate the present invention.
[0039] Example 1 A method for preparing highly topologically biomimetic decellularized leech matrix (dLE) includes the following: (1) Take a live, healthy, fresh leech and place it in an ice-water mixture for cold anesthesia for 10 minutes; then cut it longitudinally along the midline of the back, and use a scalpel and precision forceps under the assistance of a stereomicroscope to precisely peel off and thoroughly scrape away the internal digestive system, residual muscle layer and pigment layer tissue, leaving only the epidermal layer rich in connective tissue (F-LE); immerse the obtained epidermal tissue in 1×PBS buffer at 4°C and rinse repeatedly until the washing solution is clear, then cut it into standard tissue blocks of 10 mm × 5 mm for later use; (2) Primary membrane component removal (SDS treatment) Transfer the above tissue blocks to 50 mL centrifuge tubes and add 1% (w / v, g / ml) sodium dodecyl sulfate (SDS) solution at a ratio of 1 g wet tissue to 20 mL decellularized fluid. Place the centrifuge tubes in a 25°C constant temperature shaking incubator and treat at 100 rpm for 24 hours. After treatment, discard the waste liquid and add 1× PBS (7.2-7.3) solution containing 1% (v / v) penicillin-streptomycin antibiotics. Shake and wash three times at the same speed, one hour each time. (3) Secondary nucleic acid component removal (Triton X-100 treatment): After washing in step (2), discard the washing solution and add the same proportion of 1% (v / v) Triton X-100 solution to the tube. Continue shaking treatment for 24 hours under the same conditions (25°C, 100 rpm) to deeply wash away residual nucleic acids and cell debris. After treatment, wash three times with PBS solution containing double antibiotics (1 hour each time) to obtain leech decellularized matrix (dLE) that appears as a translucent milky white substance. (4) Place the dLE processed in step (3) in an ultra-low temperature freezer at -80°C overnight for pre-freezing, and then transfer it to a vacuum freeze dryer and dry it for 24 hours at -50°C and a vacuum degree of <10 Pa to obtain a porous sponge-like dry matrix dLE, which is then dried and stored in the dark.
[0040] Structural characterization 1. Quantitative analysis of decellularization efficiency (residual DNA content) Total DNA was extracted from dLE samples and fresh tissue control (F-LE) using the DNeasy Blood & Tissue Kit (Qiagen, Germany). Fluorescent staining was performed using the Quant-iT PicoGreen dsDNA detection kit.
[0041] Fluorescence intensity was measured using a fully automated biochemical microplate reader, and DNA mass concentration was calculated using a standard curve.
[0042] The results are as follows Figure 1 As shown in Figure A, H&E staining and DAPI fluorescence revealed that the dark / blue spots representing cell nuclei in the treated dLE completely disappeared; while Masson and Sirius red staining showed that the dense blue / red collagen network was well preserved. Quantitative data in Figure BD confirmed a sharp decrease in residual DNA (down to 21.33 ng / mg, removal rate >98%, with a highly statistically significant difference p<0.0001), while collagen content showed no significant loss.
[0043] Figure 1 BC analysis showed that the residual DNA level of dLE decreased to 21.33 ± 7.69 ng / mg (DNA removal rate >98%), significantly lower than the international biosafety standard of 50 ng / mg. This demonstrates the extreme success of the decellularization process of this invention. It substantially solves the safety risks of immune rejection and zoonotic diseases when xenogeneic animal tissues are implanted into the human body, perfectly preserving the natural macromolecular collagen backbone that provides mechanical support while thoroughly removing sensitized nucleic acid components.
[0044] Example 2 The chemical synthesis method of methacrylamide silk fibroin (SilMA) is as follows: (1) Thorough degumming and purification of raw silk (removal of sericin) Accurately weigh 100 g of commercial raw silk and cut it into pieces approximately 1-2 cm in length using scissors. Immerse the raw silk pieces in a 0.05 wt% sodium carbonate (Na2CO3) aqueous solution at a liquor ratio of 1:50. Boil continuously for 30 minutes in a 100°C boiling water bath. Then, pour off the yellowish waste liquid containing dissolved sericin and thoroughly wash the silk fibers with plenty of deionized water. This "boiling-washing" process must be strictly repeated 3 times to ensure that the highly allergenic sericin protein on the surface of the silk fibers is completely removed. Finally, lay the purified silk fibers flat and dry them in a 60°C forced-air drying oven for later use. (2) Homogeneous dissolution of silk fibroin Accurately weigh 20 g of the above-mentioned dried degummed silk fibroin fibers and add them to 100 mL of lithium bromide (LiBr) aqueous solution with a concentration of 9.3 mol / L. Place the reaction flask in a constant temperature water bath at 60°C, turn on the magnetic stirrer (set the speed to 300 rpm), and stir continuously for 1 hour to form a high-viscosity amber-colored homogeneous silk fibroin solution. (3) Precise grafting reaction of GMA Maintain the reaction system of step (2) in a constant temperature water bath at 60°C and a constant stirring state at 300 rpm. Slowly add a total of 3 mL of glycidyl methacrylate (GMA) to the system at a very slow constant rate of 0.5 mL / min. After the addition is complete, wrap the reaction bottle tightly with aluminum foil to protect it from light. Continue the reaction for 6 hours at the same temperature and speed to allow GMA to be fully grafted onto the amino acid residues of silk fibroin (such as serine, tyrosine, etc.). (4) Dialysis for impurity removal and freeze drying After the reaction in step (3) is completed, the mixed solution is transferred to a dialysis bag with a molecular weight cutoff (MWCO) of 8-10 kDa. The dialysis bag is completely immersed in a container filled with a large amount of deionized water and dialyzed continuously for 7 days at room temperature (25°C). During the dialysis period, the deionized water is changed 3-4 times a day to thoroughly remove lithium bromide ions and unreacted free GMA monomers from the system. The purified liquid in the dialysis tube is collected, pre-frozen overnight in an ultra-low temperature freezer at -80°C, and then freeze-dried in a vacuum freeze dryer for 48 hours to obtain a white, loose, sponge-like porous SilMA polymer. It is then stored in a sealed container at -20°C in the dark for later use.
[0045] Structural characterization 1. Take a small amount of purified lyophilized silk fibroin (SF, as a control) and the SilMA sample prepared in this example, and prepare samples using the potassium bromide (KBr) pelleting method. Heat at 4000 ~ 400 cm⁻¹- ¹ Total reflection infrared Fourier transform infrared spectrometer spectral scanning was performed within the wavenumber range.
[0046] The results are as follows Figure 2 The display shows that, compared to pure SF, the infrared spectrum of SilMA should be at 1638 cm⁻¹. - ¹ The presence of a distinct C=C double bond stretching vibration characteristic peak nearby proves that the GMA group has been successfully grafted onto the silk fibroin macromolecular backbone.
[0047] Example 3 The fabrication method of the SilMA-dLE biomimetic composite scaffold is as follows: Weigh the lyophilized dLE sample obtained in Example 1 and immerse it in SilMA prepolymer solutions with concentrations of 10% (w / v, g / mL), 20% (w / v, g / mL), and 30% (w / v, g / mL), respectively, at a solid-liquid ratio of 1 g: 5 mL. Incubate at 37 °C and 70 rpm for 24 hours (overnight) to ensure that SilMA molecules fully penetrate into the porous framework of the dLE. After incubation, remove the dLE and uniformly coat its surface with a prepolymer solution containing the corresponding concentration of SilMA and 0.2% (w / v) photoinitiator LAP. Then, perform photocrosslinking for 60 seconds using a UV lamp (wavelength 405 nm, power 25 mW / cm²) to solidify SilMA in situ into a three-dimensional network on the surface and in the pores of the dLE. After cross-linking, the composite material was repeatedly washed with deionized water to remove unreacted monomers. After freeze-drying, composite scaffolds with three concentration gradients of 10% SilMA-dLE, 20% SilMA-dLE, and 30% SilMA-dLE were obtained.
[0048] Result characterization 1. Characterization of microscopic topological structure (SEM & TEM) Scanning electron microscopy (SEM): After the freeze-dried sample was sputtered with gold by vacuum ion sputtering for 60 seconds, it was placed under a scanning electron microscope to observe the three-dimensional porous structure inside the scaffold at an accelerating voltage of 5.0 kV.
[0049] Transmission electron microscopy (TEM): The samples were double-fixed with 2.5% glutaraldehyde and 1% osmium tetroxide, embedded in epoxy resin and cut into 60-80 nm ultrathin sections. After double staining, they were placed under a transmission electron microscope and observed at an accelerating voltage of 80 kV.
[0050] The results are as follows Figure 3 Display: Cross-sectional SEM image ( Figure 3A) The distribution of the SilMA photocrosslinking network within the dLE porous framework was visually revealed. The dLE-only group exhibited a loose, open macroporous structure with clearly defined pore walls. The SilMA-dLE composite group clearly showed signs of crosslinking and filling of the polymer network within the matrix pores as the concentration of the SilMA precursor solution increased (from 10% to 30%). The scaffold porosity showed a significant concentration-dependent decreasing trend: the 10% SilMA group still retained a large pore space; while the 30% SilMA group had its pores largely filled by a dense gel network, resulting in a significant reduction in porosity. The 20% SilMA group exhibited a relatively balanced microstructure—the SilMA network was uniformly attached to the pore walls and filled some of the space, enhancing the overall structure while retaining a moderate amount of interconnected pores, avoiding complete blockage of cell migration channels due to excessive crosslinking.
[0051] 2. Biomimetic verification of the structure of dLE and rat Achilles tendon To verify the structural similarity of the leech matrix, the prepared dLE was compared with the microstructure of the decellularized rat Achilles tendon.
[0052] SEM morphology comparison ( Figure 3 B): After freeze-drying, dLE exhibited a striking structural similarity to the decellularized rat Achilles tendon. Both showed similar three-dimensional porous sponge-like structures observed on their outer surface and in cross-section, with highly similar porosity and pore size distribution. This similar microporous structure indicates that dLE, like the natural tendon matrix, can provide ideal physical space and channels for host cell infiltration, colonization, and nutrient penetration, confirming its applicability as a xenograft replacement material in terms of microscopic physical structure.
[0053] TEM ultrastructure comparison ( Figure 3 C): Under transmission electron microscopy at higher magnification, the similarity between the two extends to the collagen molecular level. The collagen fibrils inside dLE are tightly packed and aligned, and their fiber diameter and collagen-specific striation structure are highly consistent with those of rat tendon samples. This confirms that dLE not only resembles rat tendon in its micron-level pore structure (after freeze-drying), but also completely retains the natural biological characteristics in its nanoscale collagen arrangement.
[0054] 3. In order to determine the optimal SilMA crosslinking concentration, three concentration gradients of 10%, 20% and 30% were systematically evaluated from five dimensions: mechanical strength, fatigue resistance, microstructure, swelling behavior and enzymatic stability.
[0055] Measurement method: Static tensile test: The scaffold was completely immersed in PBS buffer at 37°C until swelling equilibrium was reached (simulating the wet environment in vivo). The two ends of the scaffold were fixed to the clamps of the testing machine (effective span 10 mm) and stretched at a constant speed of 5 mm / min until fracture. The ultimate breaking load and ultimate tensile strength (MPa) were recorded.
[0056] Biphasic regulation effect of SilMA concentration ( Figure 4 A / B): SilMA crosslinking significantly improved the mechanical properties of dLE, but exhibited a clear concentration dependence. When the SilMA concentration increased from 10% to 20%, the ultimate breaking load of the composite material reached its peak (15 N), an increase of approximately 87.5% compared to pure dLE (8 N), and the 20% SilMA-dLE group showed the highest ultimate tensile modulus. This is attributed to the formation of a uniform and strong interpenetrating network (IPN) between the dLE collagen network and the SilMA matrix by moderate crosslinking, which enabled efficient stress transfer through covalent bonds. However, when the concentration was further increased to 30%, the ultimate load decreased to 11 N. It is speculated that this is because the excessively high viscosity of the prepolymer hindered its uniform penetration within the dLE micropores, leading to localized defects; at the same time, the excessively high crosslinking density increased the brittleness of the material, making it more prone to brittle fracture during tension. Therefore, 20% SilMA was identified as the key balance point for optimizing mechanical properties.
[0057] The effect of (dry / wet state) on mechanical behavior Figure 4 C / D): Comparison of tensile data under dry and wet conditions revealed a significant "plasticizing effect" of moisture on the material's mechanical behavior. For the dLE, 10%, and 20% SilMA groups, the tensile modulus in the wet state decreased by approximately 10%-20% compared to the dry state, while the fracture strain increased, exhibiting typical hydrogel characteristics. However, the dry and wet moduli of the 30% SilMA group were extremely close, suggesting that its overly dense network restricted the movement of polymer chains and the penetration of water molecules. While this brought stability, it also sacrificed the material's flexibility in physiological environments, further supporting the advantage of the 20% concentration group in achieving a balance between strength and toughness.
[0058] Optimization of preparation process ( Figure 4 E / F): To ensure effective composite formation of SilMA and dLE, the effect of prepolymer soaking time was determined. Results showed that soaking dLE in SilMA solution for one day (overnight) before photocrosslinking increased the ultimate breaking load by approximately 10 N and the modulus by approximately 50% compared to the "immediate crosslinking group." This significant difference confirms that sufficient soaking time is a key process step for achieving deep penetration of SilMA molecules into the porous matrix and the formation of a homogeneous interpenetrating network.
[0059] Dynamic cyclic tensile testing: Under the same wet conditions, with the maximum strain set at 50%, 50 cyclic tensile load tests were continuously performed at a physiological frequency of 1 Hz. The area of closure of the stress-strain curve and the intensity change were recorded at the 1st and 50th tests. Main instrument: Universal testing machine equipped with a 100 N high-precision sensor.
[0060] Experimental results showed that there were significant differences in the mechanical decay behavior among different treatment groups. Figure 5 A): dLE group: Exhibited significant mechanical degradation; the curve (hysteresis loop) of the 50th cycle showed a significant rightward shift and a decrease in height compared to the 1st cycle, indicating irreversible plastic deformation and slippage of collagen fibers within the matrix. 10% and 30% SilMA groups: Although improved compared to pure dLE, a certain degree of modulus decrease was still observed (decreased curve slope). 20% SilMA-dLE group: Exhibited the best structural resilience. Its stress-strain curve of the 50th cycle almost coincided with the curve of the 1st cycle, with minimal change in hysteresis loop area, indicating that the material effectively stored and released energy during repeated deformation without significant structural damage.
[0061] Quantitative assessment of fatigue resistance ( Figure 5 B): To quantify the fatigue resistance of the 20% SilMA-dLE group, the ultimate tensile strength of the first and last tensile cycles was statistically analyzed. Initial strength: In the first tensile cycle, the 20% SilMA-dLE scaffold exhibited high mechanical strength, with an average value of 3.12 ± 0.20 MPa. Post-fatigue strength: After 50 consecutive tensile cycles at 50% maximum strain, the ultimate tensile strength remained at 2.83 ± 0.11 MPa. Although there was a slight decrease of approximately 9.3%, statistical analysis showed no significant difference in strength between the 50th cycle and the 1st cycle (ns, p>0.05).
[0062] In vitro swelling kinetics assay (confirming anti-swelling and anti-disintegration ability): Measurement Method: Accurately weigh the initial dry weight (Wd) of the lyophilized support. Immerse it in PBS buffer at 37°C, remove it at set time points (e.g., 5, 10, 30... 180 minutes), quickly blot off the free surface moisture with filter paper, and then weigh the wet weight (Ws). The swelling rate is calculated using the formula: (Ws - Wd) / Wd × 100%. Main Instrument: High-precision electronic analytical balance with a precision of 1 / 100,000.
[0063] Figure 6 (AB) shows the swelling ratio of each scaffold group after reaching equilibrium in PBS buffer. The results show that decellularization significantly altered the hydrodynamic behavior of the matrix. The dLE group exhibited the highest water absorption capacity, with an equilibrium swelling ratio as high as 671.09% ± 77.83%, significantly higher than all cross-linked groups and even slightly higher than fresh leech epidermis (F-LE group, 607.37% ± 3.25%). This high swelling phenomenon is mainly attributed to the removal of dense cellular components during decellularization, making the collagen fiber bundles more porous and exposing more hydrophilic sites, resulting in reduced osmotic resistance to water molecules. However, the swelling behavior of the composite scaffold was effectively suppressed after the introduction of the SilMA photocrosslinking network, exhibiting a significant concentration-dependent negative correlation: the swelling rate of the 10% SilMA-dLE group rapidly decreased to 394.62% ± 30.08%; the 20% SilMA-dLE group further decreased to 323.22% ± 19.06%; and the 30% SilMA-dLE group showed the lowest swelling rate, at only 282.91% ± 53.78%. This "concentration-inhibition" effect confirms that the SilMA coating constructs an effective physical confinement barrier on the dLE surface and within the pores. With the increase of SilMA concentration, the density of the crosslinking network increases, restricting the free extension of collagen chains in the hydrated state; at the same time, the relatively hydrophobic surface properties of SilMA also increase the difficulty for water molecules to enter the matrix.
[0064] Example 4 The fabrication method of the C-SilMA-dLE biomimetic composite scaffold is as follows: Step A: Under light-protected conditions, accurately weigh the SilMA lyophilized sponge prepared in Example 2 and fully dissolve it in 1× PBS (phosphate buffer) to prepare a polymer base solution with a mass-volume ratio of 20% (w / v, g / ml); then, add the natural polyphenol compound curcumin to the solution to achieve a final concentration of 80 µg / mL; and add the photoinitiator lithium phenyl-2,4,6-trimethylbenzoyl phosphate (LAP) to achieve a final concentration of 0.2% (w / v, g / ml); place the mixture in an ice-water bath and sonicate for 15 minutes until a bubble-free, orange-yellow homogeneous prepolymer solution is formed. Step B: Take the lyophilized porous dLE sheets prepared in Example 1; according to the strict solid-liquid ratio of 1 g of lyophilized dLE sheet matrix to 5 mL of prepolymer solution, completely immerse the dLE sheets in the prepolymer solution; seal the reaction vessel and incubate it overnight for 24 hours in a constant temperature shaker at 37°C and 70 rpm; Step C: The impregnated dLE film is rolled into a cylindrical shape along its long axis (i.e., the natural alignment direction of the collagen fibers), and the cylindrical strip is immediately placed in an ultraviolet curing system. An LED surface light source with a wavelength of 405 nm and an intensity of 25 mW / cm² is used to continuously and uniformly irradiate it for 60 seconds. After cross-linking, the scaffold is pre-frozen at -80°C, freeze-dried, and then sterilized by cobalt-60 radiation to obtain the finished product C-SilMA-dLE.
[0065] Result characterization 1. Characterization of surface wettability (contact angle) (confirming the Janus structure) Measurement Method: The sessile drop method was used. The finished support was cut along its longitudinal axis, exposing its outer surface (the SilMA coating side most exposed to light) and inner microenvironment on a horizontal test stage. Using a microsyringe, 5 μL of deionized water was vertically dropped onto the inner and outer surfaces respectively. A high-speed camera captured the morphology of the water droplets at the moment of contact with the material surface (e.g., 1s, 3s, 10s), and the contact angle was calculated using built-in software. Main Instrument: Contact Angle Meter.
[0066] The results are as follows Figure 7 AB analysis shows that the water contact angle on the outer surface of the finished scaffold is as high as 91.80° (exhibiting hydrophobicity, serving as a physical barrier against adhesion); while the water contact angle on the inner side of the scaffold is about 63.80° (exhibiting hydrophilicity, facilitating the penetration of cell fluid and nutrients), clearly demonstrating the successful construction of the asymmetric biomimetic interface.
[0067] Figure 7 C visually demonstrates how the thin sheet is rolled into a dense cylindrical cord along the long axis of the fiber. This proves the successful construction of the "Janus asymmetric physical anti-adhesion structure". The hydrophobic outer surface forms a strong physical wall, effectively blocking the invasion and encapsulation of exogenous fibroblasts (preventing postoperative adhesion); while the hydrophilic inner pores act like capillaries, facilitating the exchange of internal nutrients and the deep ingrowth of stem cells.
[0068] 2. Enzymatic stability of cross-linked samples Measurement Methods: The scaffolds were sterilized with ethylene oxide at 45°C and 1.7 Pa for 3 hours before evaluation. Sterile scaffold material (SilMA-dLE) was placed in PBS (10 mM, pH 7.4) and used with type I collagenase (0.1 mg / mL) to simulate the biodegradation process. All samples were placed in a 37°C shaker incubator at 100 rpm, and three replicates were examined for each group one week after degradation. During degradation, digital imaging was monitored at predetermined time intervals of 0, 3, 5, and 7 days. Simultaneously, samples were vacuum-dried and weighed 7 days after degradation, and the degradation rate was calculated. The degradation rate (BR) was calculated using the following formula: (W1–W2) / W1×100%, where W1 represents the initial sample mass and W2 represents the sample mass at the determined time point after degradation. The degradation rate of bioscaffold materials in vivo directly affects their structural support capacity in the early stages of tendon repair. To evaluate the effect of SilMA photocrosslinking coating on the stability of decellularized leech matrix (dLE), samples from each group were subjected to in vitro enzymatic hydrolysis tests in type I collagenase solution. The results are as follows: Figure 8 AB indicates.
[0069] dLE group vs. 10% SilMA-dLE group: The dLE scaffold alone is readily degraded by collagenase. Its mass rapidly decreases on day 3 of enzymatic hydrolysis, and by day 7 it is almost completely degraded, with a degradation rate approaching 100%. Notably, the degradation behavior of the 10% SilMA-dLE group is highly similar to that of the uncrosslinked dLE group, with no statistically significant difference in residual mass and final degradation rate at any time point (p>0.05). This suggests that a lower concentration (10%) of SilMA solution may not effectively shield the contact sites between collagenase and collagen fibers in the matrix due to its lower viscosity, insufficient adhesion to the dLE surface, or a sparse network structure, thus failing to significantly improve the enzymatic stability of the material.
[0070] 20% and 30% SilMA-dLE groups: With increasing SilMA concentration, the anti-enzymatic degradation ability of the composite scaffold was significantly improved. The degradation rate of the 20% SilMA-dLE group was approximately 65% on day 7, significantly lower than that of the dLE group; while the 30% SilMA-dLE group exhibited the strongest stability, with a degradation rate of only about 40% on day 7. This is attributed to the fact that the high concentration of SilMA precursor solution can form a denser and more complete polymer network under light irradiation, tightly wrapping the surface of dLE collagen fibers, and effectively blocking the attack of collagenase on the cleavage sites through intermolecular entanglement or chemical bonding, thereby delaying the degradation of the matrix.
[0071] 3. Determination of the in vitro controlled release behavior of curcumin (Cur) Media preparation: Prepare a PBS buffer containing 0.5% (v / v) Tween-80 as the release medium to increase the stability of curcumin in aqueous solution and simulate the in vivo surface active environment.
[0072] Sample incubation: Accurately weigh the C-SilMA-dLE composite scaffold prepared in Example 4 (each group contains 80 µg / mL curcumin), place it in 10 mL of release medium, and incubate in a constant temperature shaking incubator at 37℃ and 100 rpm in the dark.
[0073] Sampling and quantification: 1 mL of the release solution was taken at 1, 3, 6, 12, 24, 48, 72, 120, and 168 hours, and immediately replenished with an isothermal and equal volume of the original release medium.
[0074] Detection methods and instruments: The absorbance was measured at the maximum absorption wavelength of curcumin (425 nm) using a UV-Vis spectrophotometer. The cumulative release percentage was calculated based on the standard curve.
[0075] The results are as follows Figure 9 AB display: Figure 8 Curve A shows a smooth upward trend, and no "sudden release" phenomenon with a vertical steep increase occurred within 168 hours (7 days). Figure 8 B shows that the cumulative release reached approximately 38.57% by day 7. This demonstrates that the SilMA network constructs an extremely stable long-acting controlled-release platform. This smooth release substantially ensures that curcumin can perfectly cover the most intense "acute inflammatory storm" after tendon injury (usually in the first few days after surgery), providing a long-lasting anti-inflammatory shield.
[0076] 4. Cell biocompatibility assay Measurement Method: 1) P3 generation TDSCs were digested to prepare a single-cell suspension, and then resuspended in 1 mL of complete culture medium. After thorough mixing, 10 μL of the cell suspension was added to a hemocytometer for counting. Cells were seeded into 96-well plates. On the corresponding days of culture (day 1, day 3), 10% of the total culture medium volume of CCK-8 working solution was added to each well, and the plates were incubated at 37°C for 1.5 to 2 hours. The 96-well plates were then placed in a microplate reader, and the wavelength was measured at 450 nm. Each group had 6 replicates. In addition, a zeroing well containing only serum-free culture medium was designed. OD1 represents the OD value of the experimental group, OD2 represents the OD value of the zeroing well, and OD3 represents the OD value of the control group. The relative cell proliferation rate (CPR) was calculated as follows: (OD1–OD2) / (OD3–OD2) × 100% 2) Cell viability was determined using the Calcein-AM / PI method. Cells were seeded in 96-well plates and co-cultured with the substrate for 1 and 3 days. Calcein-AM / PI reagent was added according to the manufacturer's instructions, and the plates were then incubated at 37°C for 0.5 hours. The staining solution was removed to terminate the incubation, and 100 µL of phosphate-buffered saline was added to each well to cover the cells. Subsequently, live cells were observed to fluoresce yellow-green, while dead cells fluoresced red under an inverted fluorescence microscope, and images were taken.
[0077] The results are as follows Figure 10 As shown in Figure A, for free curcumin, cells exhibited a proliferation-promoting effect on days 1 and 2 within the concentration range of 0.4 to 2.0 μg / mL, showing a concentration-dependent effect. The 0.8 μg / mL concentration group had the most significant effect, with relative proliferation rates reaching approximately 120% and 180% on days 1 and 2, respectively, but returning to the control group level by day 3.
[0078] For the material extracts, there was no significant difference between the dLE group and the negative control group. All SilMA cross-linked extracts showed sustained proliferative activity, with the 20% SilMA-dLE group showing the most robust effect. The C-20% SilMA-dLE extract loaded with curcumin showed the strongest and fastest proliferative effect at all time points, with a proliferation rate exceeding 110% on day 1 and remaining above 130% on days 2 and 3. Figure 10 B).
[0079] Results of live and dead cell staining ( Figure 10 The results of experiments C and D are highly consistent with those of the CCK-8 assay. In the free curcumin group, the 0.8 μg / mL group showed the densest green fluorescence (live cells) on day 3 of culture, with well-spread and expanded cell morphology and very little red fluorescence (dead cells), which directly confirmed its optimal short-term cell activation effect.
[0080] In the material extract group, TDSCs co-cultured with C-20% SilMA-dLE extract for 3 days exhibited the best cell state: the highest viable cell density, cells generally exhibiting a healthy, elongated spindle shape and tight junctions, and an extremely low proportion of dead cells. The cell density or spreading morphology of other groups were inferior to this group to varying degrees, which is completely consistent with the differences in proliferation rate measured by CCK-8. The results of the two sets of CCK-8 experiments show that: Optimal window of action for curcumin: Experiments with free curcumin have clarified that 0.8 μg / mL is an optimized concentration that can effectively and significantly stimulate the proliferation of TDSCs in a short period of time, which provides a direct concentration reference for the loading target of curcumin in composite materials.
[0081] The effect of SilMA cross-linking: Compared with dLE, SilMA cross-linking treatment not only eliminated the release of potential toxic substances, but its extract also exhibited clear proliferative activity. This suggests that the cross-linking network may regulate the release of degradation products, enabling it to contain more signaling molecules beneficial to cell growth. The 20% concentration group showed the best results, further confirming the balanced nature of its cross-linking network.
[0082] Synergistic Effects and Advantages of the Composite System: The superior performance of the C-20%SilMA-dLE extract reveals the synergistic effect between the material carrier and curcumin. This composite system not only inherits the excellent background activity of the 20%SilMA-dLE extract, but more importantly, it can release curcumin in a controllable manner, forming and maintaining a near-optimal activity concentration (~0.8 μg / mL) in the local microenvironment, thus achieving a stronger and more sustained cell proliferation-promoting effect. This explains why the effect of this extract is stronger than that of the free curcumin group (whose effect subsided on day 3) and the unloaded SilMA-dLE group.
[0083] The superior proliferative properties exhibited by the C-20%SilMA-dLE extract directly confirm the effective loading and sustained release of curcumin from the scaffold. Curcumin released into the extract may, on the one hand, improve the cell culture microenvironment through its antioxidant properties; on the other hand, at specific concentrations, curcumin can regulate cell cycle-related pathways, directly stimulating stem cell proliferation. This has a significant synergistic effect with the background of the extract, rich in mild stimulating signals, provided by the SilMA-dLE matrix.
[0084] 5. Determination of the anti-inflammatory efficacy of macrophages Model construction: Mouse RAW 264.7 macrophages were used at a rate of 5 × 10⁻⁶ cells / year. 4Macrophages were seeded at a density of 100 cells / well in 24-well plates. After stimulation with lipopolysaccharide (LPS) at a final concentration of 100 ng / mL for 24 hours, macrophages were induced to polarize towards the pro-inflammatory M1 type.
[0085] Scaffold intervention: The C-SilMA-dLE scaffold was placed in a Transwell nest and co-cultured with the stimulated macrophages for 24 hours.
[0086] Supernatant collection: Collect the cell culture supernatant from each group and centrifuge at 4℃ and 2000 rpm for 10 minutes to remove cell debris.
[0087] Detection methods and instruments: Rat / mouse specific ELISA kits were used in conjunction with a fully automated biochemical microplate reader to detect the concentrations of pro-inflammatory factors IL-1β, IL-6 and TNF-α in the supernatant, strictly following the instructions.
[0088] The results are as follows Figure 11 AC analysis showed that LPS stimulation caused a dramatic surge in the concentrations of IL-1β, IL-6, and TNF-α in macrophages. However, after co-culturing with the composite scaffold of this invention, the concentrations of these three core pro-inflammatory factors all exhibited a sharp decline (inhibition rate of 55%-60%, p<0.0001). This demonstrates that the sustained-release curcumin successfully intervened in the inflammatory signaling pathway, achieving a transformation of the microenvironment from pro-inflammatory to restorative.
[0089] 6. Determination of the chemotactic recruitment capacity of endogenous tendon stem cells (TDSCs) Specific steps: Preparation of extract: The composite scaffold was extracted in serum-free culture medium for 24 hours according to ISO 10993 standard, and the extract was collected.
[0090] Migration model construction: Transwell chambers with an 8 µm pore size were used. 600 μL of composite scaffold extract was added to the lower chamber. 1 × 10⁶ scaffolds were seeded in the upper chamber. 5 TDSCs of rats.
[0091] Cell staining and counting: After incubation at 37°C for 12 hours, the chamber was removed. Unmigrated cells in the upper chamber were wiped away with a cotton swab. Cells that had crossed the membrane were fixed with 4% paraformaldehyde and then stained with 0.1% crystal violet solution for 20 minutes.
[0092] Detection methods and instruments: Five fields of view were randomly selected using an inverted phase contrast microscope to take images, and cell counting was performed using software.
[0093] The results are as follows Figure 12AB analysis showed that the average number of transmembrane migrating cells in the composite scaffold group reached 47.67 ± 2.52 cells / field, which was significantly higher than that in the control group without curcumin (approximately 22.33 cells), and the recruitment efficiency was increased by 2.1 times.
[0094] Example 5 The in situ repair of Achilles tendon defects in rats was carried out as follows: Healthy adult male SD rats aged 8 weeks and weighing 250-300 g were selected. The rats were acclimatized for one week in a standard laboratory environment with free access to food and water. Surgical procedure: Anesthesia and surgical site preparation: Inhalation anesthesia was performed using a small animal anesthesia machine. After the rats were deeply anesthetized, the hair on the right hind limb surgical area was clipped, and the area was disinfected alternately with 75% alcohol and iodine. Defect construction: A longitudinal incision (approximately 1.5 cm) was made along the lateral side of the right hind limb, and the subcutaneous tissue was bluntly dissected to expose the Achilles tendon and its surrounding tendon sheath structures. The Achilles tendon was transversely severed with a scalpel, and a 5 mm section of solid tissue was removed from the middle segment to create a large, non-healable defect model. Scaffold implantation (Kessler suture method): A cylindrical C-SilMA-dLE composite scaffold (trimmed to a length of 5 mm) prepared in Example 3 was used. Using the clinically standard Kessler suture technique, 6-0 atraumatic nylon sutures were used to securely suture and bridge the two ends of the scaffold to the proximal and distal stumps of the rat's Achilles tendon, respectively. The incision was closed: after confirming stable implantation and the absence of active bleeding, 5-0 silk sutures were used to suture the subcutaneous tissue and skin layer by layer. Postoperatively, the rats were not subjected to external plaster fixation and were allowed free movement within their cages.
[0095] Experimental groups: normal control group (NC group), simple defect control group (PC group), pure matrix group (dLE group), and C-SilMA-dLE group were set up.
[0096] 1. In vivo motor function assessment (Achilles tendon function index, AFI) Measurement Methods: Footprint analysis was performed preoperatively (-2 days) and at 2, 4, 6, and 8 weeks postoperatively. Black ink was evenly applied to the soles of both hind paws of rats. The rats were then allowed to walk along a light-blocked path lined with white paper (100 cm long, 10 cm wide), and clear, continuous footprints were collected. Three parameters were extracted: toe length (PL), toe spread (TS), and intermediate toe width (ITF). The Achilles tendon function index (AFI) was calculated using the following formula: AFI = 74 × PLF + 161 × TSF + 48 × ITF - 5, where E is the surgical side and N is the normal side.
[0097] 2. Gross anatomical and morphological evaluation Measurement method: Rats were euthanized 8 weeks post-surgery, and the original surgical path was incised. The morphology of the newly formed tissue was observed and photographed. Quantitative indicators: The width of the mid-segment of the newly formed Achilles tendon was measured using electronic vernier calipers (accuracy 0.01 mm), and a semi-quantitative score was given based on the degree of adhesion between the tissue and the surrounding skin and deep tissues (e.g., no adhesion, loose adhesion, dense adhesion).
[0098] 3. Biomechanical ultimate tensile strength test Measurement Method: The rat Achilles tendon-calcaneus complex was completely dissected. Clamps were used to fix the calcaneal side and the proximal muscle side. An effective span of 10 mm was maintained. The tensile speed was set to 5 mm / min, and loading was continued until substantial tissue fracture occurred. The stress-strain curve was recorded. Main Instrument: Universal testing machine equipped with a 100 N high-precision force sensor.
[0099] The results show Gait analysis and Achilles tendon function index (AFI) assessment, results as follows Figure 13 As shown in Figure A, the footprint length of rats in the composite scaffold group gradually shortened over time, approaching the normal preoperative morphology. Figure B shows that by 8 weeks postoperatively, their AFI index strongly rebounded to -3.98, extremely close to the normal baseline level, while the untreated group remained at the bottom of -16.68; this proves that the scaffold not only grew tissue, but also achieved a true reconstruction of biomechanical conduction function, and the animals completely overcame the lameness caused by Achilles tendon rupture.
[0100] Gross morphology and biomechanical evaluation of the newly formed Achilles tendon in rats after surgery, results are as follows: Figure 14 As shown, the macroscopic photograph in Figure A provides the highest level of visual evidence: the newly formed Achilles tendon in the composite scaffold group is a single, unbranched, dense cord with an extremely smooth surface; while the PC control group is a fleshy mass with blurred boundaries and severe adhesion to surrounding tissues. Anatomical morphology (AB): C-SilM.: A-dLE The newly formed Achilles tendon in the scaffold group appears as a single, smooth, unbranched, white, dense cord with almost no tissue adhesion on the surface; the width of the newly formed Achilles tendon is only 2.51 ± 0.18 mm, while the width of the PC group reaches 3.63 ± 0.25 mm due to fibrotic scar hyperplasia. Mechanical strength (C): The ultimate tensile stress of the newly formed Achilles tendon induced by the scaffold group of this invention reaches 8.01 ± 0.87 MPa, which is 2.9 times that of the PC group (2.76 ± 0.45 MPa). The comprehensive results demonstrate that the dual biomimetic design of this invention successfully resists the invasion of surrounding tissues (no adhesion), perfectly replicates the anatomical morphology of the Achilles tendon (no scar hyperplasia), and deposits high-strength collagen at the microscopic level (high load-bearing capacity), achieving truly clinical-grade functional regeneration of dense connective tissue.
[0101] The embodiments provided above are not intended to limit the scope of the invention, nor are the described steps intended to limit the order of execution. Any obvious modifications made to the invention by those skilled in the art based on existing common knowledge also fall within the scope of protection defined by the claims.
Claims
1. A method for preparing a leech matrix / silk fibroin biomimetic composite tendon scaffold loaded with anti-inflammatory components, characterized in that, The method includes the following steps: (1) Under light-protected conditions, methacrylamide silk fibroin was dissolved in PBS to form a polymer base solution; then, natural anti-inflammatory substances and photoinitiators were added to the polymer base solution, and the solution was subjected to ultrasonic treatment in an ice-water bath to obtain a prepolymer solution. (2) Immerse the porous leech decellularized matrix sheet completely in the prepolymer solution obtained in step (1), incubate overnight, remove it after incubation, and roll it into a cylindrical shape along the natural arrangement direction of collagen fibers. (3) The cylindrical shape obtained in step (2) is immediately placed in the UV curing system for UV crosslinking. After the crosslinking is completed, it is freeze-dried and sterilized to obtain the product.
2. The method according to claim 1, characterized in that, In step (1), the mass-to-volume ratio of methacrylamide silk fibroin in the polymer base solution is 10-30% w / v, g / ml.
3. The method according to claim 1, characterized in that, The natural anti-inflammatory substances mentioned in step (1) include one or more of curcumin, resveratrol, and quercetin.
4. The method according to claim 1, characterized in that, The concentration of the natural anti-inflammatory substance in the prepolymer solution in step (1) is 20~100µg / mL.
5. The method according to claim 1, characterized in that, The porous leech decellularized matrix sheet in step (2) is obtained by decellularizing the epidermal tissue of leeches and then freeze-drying it.
6. The method according to claim 1, characterized in that, In step (2), the ratio of the porous leech decellularized matrix sheet to the prepolymer solution is 1:5~10, g:mL.
7. The method according to claim 1, characterized in that, The overnight incubation time in step (2) is 24 hours, the incubation temperature is 37°C, and the shaking speed is 60~80 rpm.
8. The method according to claim 1, characterized in that, In step (3), the ultraviolet cross-linked LED surface light source with a wavelength of 405 nm and an illumination intensity of 25 mW / cm² is continuously and uniformly irradiated for 60 seconds.
9. The leech matrix / silk fibroin biomimetic composite tendon scaffold loaded with anti-inflammatory components prepared by the method according to any one of claims 1 to 8.
10. The application of the leech matrix / silk fibroin biomimetic composite tendon scaffold carrying anti-inflammatory components as described in claim 9 in the field of medicine and biomaterials.
